Autograft cranioplasty for the correction of a severe frontal skull defect due to hypocalvaria: A case report and review in management - Hana Ranu Herjuna; Muhammad Arifin Parenrengi; Wihasto Suryaningtyas (Romanian Journal of Neurology, 2024)
Objective. Here, the authors describe their institutional experience in managing a patient with severe frontal skull defect due to hypocalvaria with brain herniation. Material and methods. The study was conducted in the Neurosurgery Department, “Dr. Soetomo” Academic General Hospital, Surabaya, Indonesia. The neonates had a congenital anomaly, with skull defect in frontal skull duo to hypocalvaria. Defect closure with autograft cranioplasty using skull bone was performed in surgery. Outcome. The surgery was performed with autograft cranioplasty using the temporal bone on the left region. We performed decompression of the left temporal area and insertion of a ventriculo-peritoneal shunt at the right keen point to reduce intracranial pressure. Surgical treatment of patient with severe skull defect had to be done. Conclusion. Autograft with skull cranioplasty is biocompatible, as it is more easily harvested and with less infection and reaction risks.